In the Sites of Operation Condor: Memory and Afterlives of Clandestine Detention Centers. - Welch, Michael (Social Justice, 2020)
In the aftermath of the 1973 coup, Chilean intelligence agents moved to develop a security network by recruiting other nations, including the United States. In what would become known as Operation Condor, several dictatorships in the Southern Cone contributed to a centralized computerized system and data bank designed to navigate abductions, detention, torture, and ultimately assassinations. The use of clandestine detention centers became an important tool for interrogation and extermination by both Condor operatives as well as agents involved in related dirty wars. Since the early 2000s, many of those sites have been recovered by human rights groups, which have converted them into memorial spaces. This research examines the afterlives and spatial transitions of numerous such sites located in Buenos Aires (Argentina), Santiago (Chile), Asunción (Paraguay), and Montevideo (Uruguay). By doing so, interpretive commentary considers complex matters of memorialization as well as forgetting, amnesia, and denial.